Weathering the Storm! the Effects of the External Environment on Police Efficiency in Peru - Dammert-Guardia, L (Emerald Group Holdings Ltd., 2019)
Purpose: The purpose of this paper is to examine the effect of external factors on police efficiency in a sample of Peru’s municipalities. Drawing on the postulates of the contingency theory of organizations, this study argues that because of the public nature of police organizations’ activities, they are heavily influenced by the environment in which they operate, which invariably affects their efficiency. Design/methodology/approach: The study examines police efficiency using a four-stage Data Envelopment Analysis model in a sample of 619 Peruvian municipalities (“distritos”). After adjusting the inputs to the external environment, the remaining inefficiencies are presumed to result from managerial issues and other internal organizational factors. Findings: The results indicate that police efficiency improves after adjusting police inputs to the effect of external factors. The mean efficiency scores improved by 39 percent from 0.57 to 0.79. Because the effects of the external environment can be stronger in larger municipalities, these experience larger improvements in efficiency than smaller municipalities. Research limitations/implications: There are two important limitations. First, the sample of municipalities in Peru is limited and the results must be interpreted with caution. In addition, the external factors included in the second stage analysis represent only a proportion of all potential external factors which can influence police efficiency. Second, the results presented here explain only one aspect of contingency theory. An important implication of this study suggests that for police managers to make more informed decisions on resource use and allocations, they need a more thorough understanding of the environments in which police operate. Social implications: It can assist researchers to ascertain the effects of the external environment on police performance. More importantly, it can assist police managers in making informed decisions about resource use and allocation. Consequently, a better use of resources could lead to better policing and improved citizen safety and security. Originality/value: This study introduces a new and innovative methodological approach to measure police performance. This multi-stage approach has not been used in the context of democratic policing in Latin America and the Caribbean. The current research fills an important gap on how to measure police performance in developing countries. © 2019, Emerald Publishing Limited.